Fibrinogen Haifa: Fibrinogen Variant with Absence of Protective Effect of Calcium on Plasmin Degradation of Gamma Chains - Soria, J; Soria, C; Samama, M; Tabori, S; Kehl, M; Henschen, A; Nieuwenhuizen, W; Rimon, A; Tatarski, I (Thrombosis and Haemostasis, 1987)
The abnormal fibrinogen Haifa is characterized by the fact that calcium present during enzymatic digestion by plasmin does not protect the Haifa D gamma chain against further plasmin attack as it does in normal molecules.Since calcium binding to fibrinogen, ADP - platelet aggregation cofactor activity and gamma dimerization process induced by factor XIIIa are normal for fibrinogen Haifa, the corresponding sequences in the gamma chain are not involved. It seems rather that the anomaly resides near the gamma 302 plasmin cleavage site that is protected when calcium is bound to the gamma chain and that this affects the availability of the polymerization site located in the C terminal part of the chain.
Keywords: Dysfibrinogenemia; Fibrinogen; Fibrinogen degradation products; Fibrinolysis